2016
DOI: 10.5762/kais.2016.17.2.436
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ego-Resilience, Critical Thinking Disposition, and Self Leadership on Career Decision-Making Self-Efficacy in Nursing Students

Abstract: This study examined the effects of ego-resilience, critical thinking disposition, and self leadership on the career decision-making self-efficacy among nursing students. Undergraduate nursing students (N=341) were sampled randomly from nursing departments in two cities. Data collection was conducted from May 11 to June 5, 2015. The participants completed a questionnaire assessing the ego-resilience, critical thinking disposition, self leadership, and career decision-making self-efficacy. The data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…The scenario reflected the common contents extracted by literature review and interviews, which included how to wear the PPE, a nursing interview and sample collection and packaging. The VR simulation education in this research adopted the protocol of a simulation study for the patients with respiratory infections (Kim & Song, 2019) consisting of three steps, including prerequisite learning, VR simulation education program drive and debriefing for 85 min.…”
Section: Program Designmentioning
confidence: 99%
“…The scenario reflected the common contents extracted by literature review and interviews, which included how to wear the PPE, a nursing interview and sample collection and packaging. The VR simulation education in this research adopted the protocol of a simulation study for the patients with respiratory infections (Kim & Song, 2019) consisting of three steps, including prerequisite learning, VR simulation education program drive and debriefing for 85 min.…”
Section: Program Designmentioning
confidence: 99%
“…Introspective experiences play an essential role in the reintegration of resilience [8], where self-reflection or introspection is an aspect of critical thinking disposition [62]. Research indicates that critical thinking disposition is associated with ego resilience in South Korean nursing students [72]. Other studies have found that cognitive ability and thinking disposition significantly predict belief bias in syllogistic reasoning [73].…”
Section: Metacognitive Experience Critical Thinking Disposition and R...mentioning
confidence: 98%
“…연구가 점차 증가되고 있다 [8,[10][11][12][13][14][15][16][17][18][19][20][21]. 특히 간호학사학위 교육과정의 일 환으로 간호대학생의 진로탄력성 향상을 위한 CPDP 연구는 매우 제 한적으로 진행되어왔다 [8,10,[12][13][14][15].…”
Section: 로그램(Career Planning and Development Program Cpdp) 개발을 위한unclassified
“…특히 간호학사학위 교육과정의 일 환으로 간호대학생의 진로탄력성 향상을 위한 CPDP 연구는 매우 제 한적으로 진행되어왔다 [8,10,[12][13][14][15]. 간호대학생의 진로탄력성 관련 요 인으로는 진로결정자기효능감과 진로결정수준 [12][13][14][15][16][18][19][20][21] • 대상자의 일반적 특성에 따른 진로결정자기효능감, 진로결정수준 및 진로탄력성의 차이를 파악한다.…”
Section: 로그램(Career Planning and Development Program Cpdp) 개발을 위한unclassified